Probabilistic analysis of the effect of shot peening on the high and low cycle fatigue behaviors of AA 7050-T7451. (June 2018) - Bianchetti, C.; Lévesque, M.; Brochu, M.
Highlights: The effect of shot peening media and intensity on fatigue life is proposed. A probabilistic analysis of fatigue life data is proposed. Surface roughness and crack initiation mechanisms were analyzed. Trace of Zirconium contamination were found on surface peened with Z425 shots. Abstract: Fatigue tests and probabilistic analysis were carried out on aluminum alloy 7050-T7451 samples having surface conditions of as-polished, as-machined, and shot peened. Different combinations of media and intensity were studied. Fatigue tests were carried out in the high and low cycles fatigue regimes. Fatigue life dispersion was analyzed and tolerance limits, such as the 50% and 90% survival rates at 95% confidence level, were computed. Fatigue results dispersion after peening was the smallest for conditioned cut wire shots CW14. Samples peened with ceramic Z425 shots had the largest fatigue life dispersion. Comparison of surface roughness parameter, with fatigue life dispersion and shot diameters indicates that smaller shots create rougher surfaces responsible for premature crack initiation. Fatigue life reliability (best trade-off of fatigue life dispersion and mean values) depended on the tested Almen intensity and stress amplitudes. At high stress amplitude, cast steel shot S230 was the most reliable condition because of the smooth surface it induced. At low stress amplitude, peening with ceramic Z425 shots at an intensity of 8A was the most reliable condition, while it was the least reliable in high cycle fatigue. The fractography analysis, completed for every condition, revealed shot contamination on samples peened with Z425 shots at an intensity of 8A and tested at high stress amplitude, which could be responsible for the deterioration of the fatigue properties.